2015
DOI: 10.1016/j.contraception.2014.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Achieving cost-neutrality with long-acting reversible contraceptive methods

Abstract: Objectives This analysis aimed to estimate the average annual cost of available reversible contraceptive methods in the United States. In line with literature suggesting long-acting reversible contraceptive (LARC) methods become increasingly cost-saving with extended duration of use, it aimed to also quantify minimum duration of use required for LARC methods to achieve cost-neutrality relative to other reversible contraceptive methods while taking into consideration discontinuation. Study design A three-stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 13 publications
0
49
0
1
Order By: Relevance
“…Thus, provider-patient interactions play a critical role in an individual's decision to use an effective contraceptive method (Dehlendorf, Kimport, Levy, & Steinauer, 2014a;Kavanaugh, Frowirth, Jerman, Popkin, & Ethier, 2013). Finally, because effective contraceptive methods can have prohibitively high up-front costs, economic capital is an important factor in considering certain methods over others (Dennis & Grossman, 2012;Trussell, Hassan, Lowin, Law, & Filonenko, 2015).…”
Section: Effective Reversible Contraceptive Methodsmentioning
confidence: 99%
“…Thus, provider-patient interactions play a critical role in an individual's decision to use an effective contraceptive method (Dehlendorf, Kimport, Levy, & Steinauer, 2014a;Kavanaugh, Frowirth, Jerman, Popkin, & Ethier, 2013). Finally, because effective contraceptive methods can have prohibitively high up-front costs, economic capital is an important factor in considering certain methods over others (Dennis & Grossman, 2012;Trussell, Hassan, Lowin, Law, & Filonenko, 2015).…”
Section: Effective Reversible Contraceptive Methodsmentioning
confidence: 99%
“…Although continuation rates in this study were somewhat lower than shown in some prior studies, we found a median use of >3 years. Modeling studies have shown that IUDs become among the most cost-effective methods after 3 years of use 4 ; therefore, even with the typical use seen in our study, IUDs are still among the most cost-effective contraceptive methods. Continued efforts to increase uptake and continuation of IUDs will improve women's ability to control their reproduction and result in cost savings for the health system.…”
Section: Commentmentioning
confidence: 52%
“…3 IUDs are highly cost-effective contraceptives. 4 Given their high efficacy, ease of use, and cost-effectiveness, IUDs have great potential to prevent undesired pregnancy 5 and to allow women to exercise autonomy over their reproductive health.…”
Section: Introductionmentioning
confidence: 99%
“…When considering additional benefits from preventing unintended pregnancies not desired at a later time, the intervention is cost-saving in all scenarios. Previous studies have shown that expanding access to contraception, especially LARC, is cost-saving ( 16 , 37 , 38 ). Likewise, our findings suggest that this intervention could be cost-saving or cost-effective within the context of a public health emergency response.…”
Section: Discussionmentioning
confidence: 99%
“…The latter comprised the costs of contraception methods and related office visits and services (e.g., insertion and removal of LARC for new method users resulting from the intervention and the cost of more intensive counseling for all women receiving contraceptive services during the intervention). We took the 1-year costs for contraception methods from the literature ( 16 , 29 ) and based the other program costs on the estimated costs for a pilot program planned to increase access to contraception in Puerto Rico as part of the current Zika virus outbreak response ( 30 ). We did not apply a discount rate to intervention costs because of the time horizon of 12 months.…”
Section: Methodsmentioning
confidence: 99%